Interpretation of 3 D Magnetic Inversion Results in the Majenang Area, Indonesia - Accep Handyarso (Department of Physics, Sebelas Maret University, 2025)
The Total Magnetic Intensity (TMI) data requires conversion using Reduction to Pole (RTP) or Reduction to Equator (RTE) filters prior to the interpretation process. However, the low latitude location causes stability issue in the RTP and is replaced by the RTE computing processes. Noteworthy, the RTE results have inverted polarity. An inverse modeling scheme based on direct use of TMI data using equivalent‑source provides an alternative solution to address this issue. In this research, synthetic modeling of a strike‑slip fault geometry is conducted to assist the interpretation process in order to guide during recognizing similar anomaly contour patterns in field datasets. TMI data interpretation was conducted in a volcanic area located in Majenang, Central Java. According to the research findings, a dextral strike‑slip fault with a northwest‑southeast lineament is delineated. This fault is interpreted as part of the Pamanukan‑Cilacap Fault Zone (PCFZ). Additionally, a circular anomaly is exposed and inferred to be the edge of ancient‑volcanic‑caldera (ring‑fault or caldera‑rims) in the study area. Both results were confirmed through a comparison of geomagnetic and gravity data. The high‑susceptibility zone correlates well with the high‑density zone and the outcrop of the Sangkur Volcano's intrusion body, which is inferred precedes the intrusion body of the Kumbang Volcano. The intrusive bodies located around the PCFZ manifest the presence of a weak zone that has been intruded by magmatism, contributing to the formation of volcanoes along the fault as a volcano‑tectonic setting in the area.